2008
DOI: 10.1348/014466508x279260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mindful and non‐mindful exercises on people with depression: A systematic review

Abstract: We recommend that more well-controlled studies have to be conducted in the future to address the short- and long-term effects of physical exercise on alleviating depression. Efforts should be focused on unveiling the differential effects of mindful and non-mindful exercises on depression and the underlying mechanisms of their therapeutic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 55 publications
1
81
0
3
Order By: Relevance
“…By encouraging mindfulness and offering a method to address the current mood, participants reported that their confidence increased as they progressed through the study. Physical activity can be highly effective at decreasing depression but it can be difficult for depressed individuals to immediately move into an active routine (Dunn, Trivedi, Kampert, Clark, & Chambliss, 2005; Larun, Nordheim, Ekeland, Hagen, & Heian, 2006; Tsang, Chan, & Cheung, 2008); the intervention was designed such that the yoga movements progressed in difficulty throughout the 8-week intervention, helping individuals feel more competent. The introduction of coping methods for dealing with maladaptive ruminations and for enhancing a sense of competence is imperative for diminishing symptoms of depression in women (Smith & Alloy, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By encouraging mindfulness and offering a method to address the current mood, participants reported that their confidence increased as they progressed through the study. Physical activity can be highly effective at decreasing depression but it can be difficult for depressed individuals to immediately move into an active routine (Dunn, Trivedi, Kampert, Clark, & Chambliss, 2005; Larun, Nordheim, Ekeland, Hagen, & Heian, 2006; Tsang, Chan, & Cheung, 2008); the intervention was designed such that the yoga movements progressed in difficulty throughout the 8-week intervention, helping individuals feel more competent. The introduction of coping methods for dealing with maladaptive ruminations and for enhancing a sense of competence is imperative for diminishing symptoms of depression in women (Smith & Alloy, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the factors associated with depressive symptoms were: high levels of job stress, problem drinking, insufficient sleep, lack of social support and absence of stress reduction techniques over both genders, such as lack of physical exercise and sedentary lifestyle. A wide range of studies have shown that regular physical exercise reduces stress symptoms, mood disorder, anxiety and depressiveness (Broman-Fulks and Storey 2008;Janisse et al 2004;Smith et al 2007;Tsang et al 2008;Wang et al 2010). Acute resistance exercise induced catecholaminergic rather than HPA axis stimulation (Fatouros et al 2010).…”
Section: Physical Exercise As Interventionmentioning
confidence: 99%
“…Less research has evaluated mechanisms that may contribute to improvements in non-motor function. TCQ related improvements in depression and anxiety have been hypothesized to be related to modest cardiovascular loading, breathing and imagery related changes in autonomic tone, cognitive restructuring leading to reduced rumination and catastrophizing, and indirect effects of enhanced motor confidence and enhanced self-efficacy [11, 3133]. These mechanisms, as well as multi-tasking and attention shifting training associated with TCQ, have been hypothesized to contribute to enhanced cognitive function [34], and some studies have reported correlations between TCQ-related improvements in cognitive function and brain neural architecture and resting state neural network activity [35, 36].…”
Section: Introductionmentioning
confidence: 99%